Separation of cyclic lipopeptide puwainaphycins from cyanobacteria by countercurrent chromatography combined with polymeric resins and HPLC - Cheel, José; Urajová, Petra; Hájek, Jan; Hrouzek, Pavel; Kuzma, Marek; Bouju, Elodie; Faure, Karine; Kopecký, Jiří (Analytical and bioanalytical chemistry, 2017)
Puwainaphycins are a recently described group of β-amino fatty acid cyclic lipopeptides of cyanobacterial origin that possess interesting biological activities. Therefore, the development of an efficient method for their isolation from natural sources is necessary. Following the consecutive adsorption of the crude extract on Amberlite XAD-16 and XAD-7 resins, countercurrent chromatography (CCC) was applied to separate seven puwainaphycin variants from a soil cyanobacterium (Cylindrospermum alatosporum CCALA 988). The resin-enriched extract was first fractionated by CCC into fractions I and II with use of the n-hexane-ethyl acetate-ethanol-water (1:5:1:5, v/v/v/v) system at a flow rate of 2 mL min-1 and a rotational speed of 1400 rpm. The CCC separation of fraction I, with use of the ethyl acetate-ethanol-water (5:1:5, v/v/v) system, afforded compounds 1 and 2. The CCC separation of fraction II, with use of the n-hexane-ethyl acetate-ethanol-water (1:5:1:5, v/v/v/v) system, afforded compounds 3-7. In both cases, the lower phases were used as mobile phases at a flow rate of 1 mL min-1 with a rotational speed of 1400 rpm and a temperature of 28 °C. The CCC target fractions obtained were repurified by semipreparative high-performance liquid chromatography (HPLC), leading to compounds 1-7 with purities of 95 %, 95 %, 99 %, 99 %, 95 %, 99 %, and 90 % respectively, as determined by HPLC-electrospray ionization high-resolution mass spectrometry (ESI-HRMS). The chemical identity of the isolated puwainaphycins (compounds 1-7) was confirmed by ESI-HRMS and NMR analyses. Three new puwainaphycin variants (compounds 1, 2, and 5) are reported for the first time. This study provides a new approach for the isolation of puwainaphycins from cyanobacterial biomass. Graphical Abstract Separation of cyclic lipopeptide puwainaphycins from cyanobacteria by countercurrent chromatography combined with polymeric resins and HPLC. Compounds 1 (12-hydroxy-4-methyl-Ahtea-Puw-F), 2 (11-chloro-4-methyl-Ahdoa-Puw-F), 3 (4-methyl-Ahdoa-Puw-F), 4 (4-methyl-Ahdoa-Puw-G), 5 (12-chloro-4-methyl-Ahtea-Puw-F), 6 (4-methyl-Ahtea-Puw-F) and 7 (4-methyl-Ahtea-Puw-G). Ahtea: 3-amino-2-hydroxy tetradecanoic acid. Ahdoa: 3-amino-2-hydroxy dodecanoic acid.
Keywords: Cyanobacteria; Lipopeptides; sinice; Cyclic lipopeptides; Puwainaphycins; Biomass; Countercurrent Distribution; vysokoúčinná kapalinová chromatografie; protiproudá chromatografie; Countercurrent chromatography; lipopeptidy; magnetická rezonanční spektroskopie; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, High Pressure Liquid; cyklické peptidy; Centrifugal partition chromatography; Peptides, Cyclic; Magnetic Resonance Spectroscopy; biomasa; Spectrometry, Mass, Electrospray Ionization